Cardiovascular factors are related to dopamine integrity and cognition in aging. Issue 11 (30th October 2019) - Karalija, Nina; Wåhlin, Anders; Ek, Jesper; Rieckmann, Anna; Papenberg, Goran; Salami, Alireza; Brandmaier, Andreas M.; Köhncke, Ylva; Johansson, Jarkko; Andersson, Micael; Axelsson, Jan; Orädd, Greger; et al.
Abstract: Objective: The aging brain undergoes several changes, including reduced vascular, structural, and dopamine (DA) system integrity. Such brain changes have been associated with age‐related cognitive deficits. However, their relative importance, interrelations, and links to risk factors remain elusive. Methods: The present work used magnetic resonance imaging and positron emission tomography with 11 C‐raclopride to jointly examine vascular parameters (white‐matter lesions and perfusion), DA D2‐receptor availability, brain structure, and cognitive performance in healthy older adults ( n = 181, age: 64–68 years) from the Cognition, Brain, and Aging (COBRA) study. Results: Covariance was found among several brain indicators, where top predictors of cognitive performance included caudate and hippocampal integrity (D2DR availability and volumes), and cortical blood flow and regional volumes. White‐matter lesion burden was negatively correlated with caudate DA D2‐receptor availability and white‐matter microstructure. Compared to individuals with smaller lesions, individuals with confluent lesions (exceeding 20 mm in diameter) had reductions in cortical and hippocampal perfusion, striatal and hippocampal D2‐receptor availability, white‐matter microstructure, and reduced performance on tests of episodic memory, sequence learning, and processing speed. Higher cardiovascular risk as assessed by treatment for hypertension, systolic blood pressure, overweight, and smoking was associated with lower frontal cortical perfusion, lower putaminal D2DR availability, smaller grey‐matter volumes, a larger number of white‐matter lesions, and lower episodic memory performance. Interpretation: Taken together, these findings suggest that reduced cardiovascular health is associated with poorer status for brain variables that are central to age‐sensitive cognitive functions, with emphasis on DA integrity.